SOUND PATTERN OF INDONESIAN PLOSIVES - Huili Li; I Praptomo Baryadi; I Dewa Putu Wijana (Linguistik Indonesia, 2019)
As a language which is quite extensively used, Indonesian segments are already known to linguists. Although experimental research methodology is relatively new, it is useful for undertaking further research on Indonesian phonology and phonetics. It can assist in generating phonological and phonetic data as evidence of sounds within a theoretical framework. Sound pattern study by means of experimentation is selected as the theoretical framework for this research. As sound patterns of one language consist of many subparts, this research only focuses on the Indonesian plosive sound pattern. This paper examines sound pattern of Indonesian plosives and their special features. In order to do this research, a quantitative method is adopted for data collection and analysis. Indonesian words with plosives at the beginning of the second syllable and first syllable are respectively designed as stimuli for recordings. Then sound analysis software Praat is applied to measure gap and the voice onset time of plosives as parameters of data. The result of this research shows that the Indonesian plosive sound pattern forms two clear clusters on an acoustic plosive chart. Voiceless plosives have a longer gap duration than their corresponding voiced plosives. Front plosives in the vocal cavity have a longer gap than back plosives, but are shorter in VOT length. Such acoustic results will provide the basis for further research such as auditory phonetics experimental research and second language acquisition. Additionally, the visualization of abstract concepts, compared to the Chinese sound pattern, will help Indonesian learners from China better understand the Indonesian sound pattern and Indonesian language teachers to seek better solution to students’ pronunciation problems.